Assessment of Process Improvement Potential of Carbon Dioxide as a Cryogenic for Machining Operations - Gross, Daniel; Hanenkamp, Nico; Heinz, Andrea; Ebner, Martin (Applied Mechanics and Materials, 2017)
Cryogenic machining offers advantages compared to conventional cooling lubrication strategies particularly for difficult-to-cut and high-temperature-resistant materials such as titanium and nickel alloys. For implementation purposes environmental and cost factors are crucial for this new machining approach in series production. In order to facilitate investments it is mandatory to evaluate the technology’s potential prior to the final implementation decision. In the field of machining, in particular machining with cryogenic process cooling, there is no standardized and uniform procedure to assess this potential. In this paper a systematic approach and underlying analysis tool will be introduced to determine the potential of cryogenic processing in terms of resources and energy efficiency of the manufacturing operation. This approach satisfies the general conditions in a reasonable assessment effort as well as in the detail level. With this analysis tool, real production and process data are compared with results from scientific cryogenic tests and research and examined with regards to their applicability. Thus, it is possible in an early stage of the production to identify potentials in manufacturing and to take measures to realize these effects. In case cryogenic processing of a specific material has not been carried out so far, the similarity of this material to existing research results is determined. If positively assessed, the surrogates’ potential is transferred with a specific safety factor to the material. The analysis tool has been applied and refined in a real large-scale series production as well as in a complex component manufacturing and the holistic potential for e. g. durability, material removal rate (MRR) or savings regarding the use of metal working fluids (MWF) have been identified.
Keywords: Carbon Dioxide; Cryogenic Machining; Large Scale Series Production; Potential Assessment

Bauteilfinishing durch CO2-Trockeneisstrahlen - Automatisierbare Nachbearbeitungsprozesse durch innovative Fertigungstechnologien - Amon, Sven; Gross, Daniel; Hanenkamp, Nico (wt Werkstattstechnik - Online, 2019)
Zur Produktivitätssteigerung ist eine ganzheitliche Optimierung von Prozessketten erforderlich. Auch innovative Fertigungstechnologien wie die additive Fertigung fordern ressourcenintensive und nicht-wertschöpfende Nachbearbeitungsprozesse. Das Entfernen von verfahrensbedingten Fertigungsrückständen sowie Materialanhaftun-gen wie Stützstrukturen ähnelt der Gratbeseitigung subtraktiver Fertigung. Für beide Herausforderungen bieten CO2-basierte Strahl-verfahren einen effizienten Lösungsansat
Keywords: Fertigungstechnik; Additive Fertigung; Automatisierung

Comparison of linear and trochoidal milling for wear and vibration reduced machining - Gross, Daniel; Friedl, Fabian; Meier, Trixi; Hanenkamp, Nico (Procedia CIRP, 2020)
Vibrations during milling lead to frequent tool replacements. This results in an unsteady load on the machine, which leads to increased tool wear, poor surface quality and therefore strong economic and ecological burden. Self-excited vibrations are influenced by the machining conditions, such as the workpiece geometry or the tool path generated by the used computer-aided manufacturing (CAM) software. This article compares linear and trochoidal milling in terms of vibration behavior and resulting wear phenomena by machining different component geometries. The results show, that trochoidal milling is not a suitable strategy to reduce vibrations and tool wear compared to linear milling.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CAM; Milling; Milling strategy; Tool path optimazation; Vibration; Wear

Comparison of sprayability and solubility of bio-based lubricants with liquid carbon dioxide - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
In recent years, cryogenic minimum quantity lubrication (CMQL) has been established in comparison to pure cryogenic cooling. The used oil has a crucial influence on the success of the technology. The aim of this study is to investigate the influence of oils from renewable resources with regard to their miscibility with carbon dioxide (CO2) and their spraying behavior. Ten different bio-based oils (synthetic ester, natural ester and fatty alcohol) have been examined regarding their suitability for CMQL compared to a conventional mineral hydrocrack oil. A validation based on sprayability and solubility properties with liquid CO2 has been performed. The sprayability and the resulting oil droplet size have an impact on the amount of oil entering the process zone and thus on the lubrication performance of the coolant concept. For this reason, a high-speed camera has been used to capture shadow images of the jet from an external cooling nozzle. In addition the width, intensity and uniformity of the oil application were evaluated. The solubility of the bio-based oils in CO2 is investigated in a static mixing chamber with varied mixing ratio. The miscibility of the bio-based oils in a single channel supply system was investigated with high-speed recordings of a dynamic mixing chamber. The results of the various experimental setups have been compared.<br
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide

Cutting force and vibration prediction of milling processes regarding the nonlinear behavior of cascade controlled feed drives - Ju, Shu; Gross, Daniel; Hanenkamp, Nico (Production Engineering, 2022)
Milling processes are characterized by their high degree of flexibility regarding shape creation and thus occur in many value adding processes in the electrical and mechanical engineering industry. To facilitate the systematic prediction and the efficient optimization of the process performance, a holistic simulation model of the milling process with cascade controlled feed drives is developed. The integrated model consists of two subsystems, namely the feed drive model and the process model. In the feed drive model, the dynamic models of the electric motors, the serially connected torsional oscillators of the mechanical elements and the cascade control system are established. In this model, the coordinate point of the milling tool is computed at each discrete time step and assigned to the process model. The cutting forces and the corresponding load torques are calculated in the process model and sent back to the feed drive model. In addition, practical validation of the complete system has been conducted both in the time and the frequency domain. The simulation results yield an accurate prediction of the tooth passing frequency with a variance of less than 1%. Moreover, the influence of the cascade control parameters and the nonlinear behavior of the electric motor on the process vibrations have been experimentally verified.<br
Keywords: Milling process simulation; Cascade control model; Cutting force prediction; Vibration prediction

Demonstration of a new approach for measuring tools with the impingement sound of an air jet using machine learning - Würschinger, Hubert; Gross, Daniel; Stadler, Manuel; Mühlbauer, Matthias; Hanenkamp, Nico (MM Science Journal, 2021)
Monitoring the tool condition of machining processes is important but challenging. Several automated tool condition monitoring solutions are available, but often not used due to existing restrictions or disadvantages. A new approach can be the detection and measurement of tool conditions analyzing the sound of an air jet impingement on tools. Due to the availability of compressed air as a working and cleaning medium for many processes, this approach can be used for various condition monitoring and measuring tasks. In this paper the procedure and its functionality are first presented on simple shapes and then tested on the tool wear of inserts.<br
Keywords: Tool Condition Monitoring; Condition Monitoring; Impingement Sound; Jet Impingement; Air Jet; Flow Noise; Airborne Sound; Machine Learning

Effect of various cooling lubricant strategies on turning Inconel 718 with different cutting materials - Ostrowicki, Nicolai; Kaim, Alexander; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2021)
Due to its resistance to high temperatures and corrosion, Inconel 718 has a wide range of applications, particularly in the chemical and aerospace industry. The aim of this study is to investigate the potential of turning Inconel 718 with regard to tool life, depending on various cooling lubricant strategies and cutting materials. The reference process is flood cooling with carbide tools. Based on this, the process with carbide and CBN tools under dry machining, cryogenic cooling and cryogenic minimum quantity lubrication will further be investigated. Cutting forces, tool wear, roughness and chips are analyzed. Cutting length, surface quality and sustainability can be improved by using CBN and cryogenic minimum quantity lubrication (CMQL).<br
Keywords: Inconel 718; CBN; turning; cryogenic; cryogenic minimum quantity lubrication

Energy Efficiency Assessment of Cryogenic Minimum Quantity Lubrication Cooling for Milling Operations - Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2021)
Cryogenic minimum quantity lubrication (CMQL) extends the application spectrum of cryogenic cooling by the possibility of lubrication. This enables the proportion of both cooling and lubrication capacity to be adapted to the process as required. Especially liquid CO2 has been established for the CMQL. This application enables a sustainable use of CO2 in a circular cycle opposed to its emission to the atmosphere. For a comparison of conventional flood cooling with CMQL, the specific energy has to be determined in addition to the process-related suitability. Specifications by the European Commission and the desire for sustainable production require a quantification of the environmental impact. For the determination of these product carbon footprints, energy demand forecasts are essential. This paper presents a method for calculating the energy demand for milling processes under CMQL and wet machining according to the life cycle assessment EN ISO 14044 taking the material flows into account. The considered material flows include the cutting energy of the process, the energy to provide the water for the emulsion for flood cooling, the energy to liquefy the CO2, the energy for the oil refining process for emulsion and CMQL, the energy for the coolant pumps and the energy for the manufacturing of the tools. The balancing is carried out for a defined functional unit. Due to the different tool lifetimes, there are large fluctuations in the energy requirements. It is shown that despite the high energy expenditure for the provision of CO2 and the energy supply for flood cooling, the most significant influence on the energy expenditure results from the manufacture of the tools. By increasing the tool life and increasing the number of tool regrinding cycles, the energy requirement for the functional unit can be reduced.<br
Keywords: CMQL; flood cooling; energy efficiency; LCA; milling

Erweitertes Prozessverständnis erleichtert das Bauteilfinishing - Amon, Sven; Pour Abdollahyan, Fardin; Gross, Daniel; Hanenkamp, Nico (Werkstatt und Betrieb, 2019)
Das Finishing steht durch vorwiegend manuelle Bearbeitungskonzepte im Widerspruch der Automatisierungstrends. Neue Erkenntnisse zum Finishen mit Trockeneis ermöglichen Anwendern Ansätze für leicht zu automatisierende Technologien bereits im Vorfel
Keywords: Entgraten; Abtragen von Stützstrukturen; Reinigung; Finishing; Automatisierung

Hybrid Supply System for Conventional and CO2/MQL-based Cryogenic Cooling - Hanenkamp, Nico; Gross, Daniel; Amon, Sven (Procedia CIRP, 2018)
Increasing demand for difficult-to-cut materials challenge conventional cooling techniques to their limit. The durability of the tool is often reduced and cutting parameters such as feed rate or depth of cut have to be adjusted with a negative impact on productivity. Therefore, innovative cooling technologies have to be developed and integrated into new and existing machining equipment. The article describes the development of a hybrid cooling concept offering the flexibility to assign conventional or cryogenic cooling to incremental process steps. The developed cryogenic cooling supply system controls the flow of liquid carbon dioxide regarding density, flow rate and temperature before the lubrication media is injected by a high precision pump into the same tube. This approach significantly reduces the integration effort especially for internal cooling before being applied to a drilling process with a rotating tool of 50CrMo4. The challenges for the integration in the machine tool consist in the interface between spindle and tool holder and the tool itself due to the potential expansion of CO2 leading to undesired cooling before reaching the tool center point. Therefore, each interface has been investigated and requirements for cryogenic-compatible tools have been defined. Finally, different lubrication fluids combined with CO2-based cryogenic cooling have been investigated regarding tool durability for a milling process of Ti6Al4V. The results show that different oils have significant impact on the process performance offering a perspective for further research.<br
Keywords: Cryogenic Cooling; Minimum Quantity Lubrication

Influence of Additivation of Bio-Based Lubricants on Sprayability and Solubility for Cryogenic Minimum Quantity Lubrication - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
The development of innovative cooling lubrication strategies is significantly driven by the need to machine materials resistant to high temperatures while taking into account both ecological and economic aspects. Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in the manufacturing process. A minimal amount of oil is added to the cryogenic medium carbon dioxide (CO2) to ensure both cooling and lubrication during tool engagement. In this context, vegetable oils, so-called triglycerides, can be used with respect to the cooling lubrication concept. The aim of this paper is to analyze various bio-based oils with regard to their solubility, spraying and flow behavior and to investigate the influence of additives on the performance. During the lubrication tests, the additives have shown no influence on the lubricating effects. Thus the chemical properties of the base oils primarily influence the properties with regard to solubility and spray behavior. Finally, the collected results were correlated with machining tests showing only a limited correlation with the aforementioned lubrication tests.
Keywords: CMQL; Milling; Liquid carbon dioxide; Bio-based lubricants

Influence of Carbon Dioxide Temperature on Sprayability and Solubility in Cryogenic Minimum Quantity Lubrication with Bio-Based Lubricants - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in many manufacturing processes. In previous series of experiments a variation of the thermodynamic state of the cryogenic medium taken from riser bottles could be observed. Consequently, the aim of this study was to specifically control the thermodynamic state of the CO2 and, associated with this, the density after removal from the riser bottles. To achieve this objective conventional cooling was implemented for the CO2 after withdrawal from the riser bundle in order to have a constant liquid state of the CO2 during feeding. The density of the cryogenic medium could be raised from ρ = 550 kg/m3 to over 800 kg/m at a mass flow rate of m˙ CO2 = 5 kg/h with the applied cooling method and can also be stabilized regarding the density pulsation. Subsequently, the effects of temperature-controlled CO2 on the sprayability and solubility in CMQL were examined and resulted in increased atomization of the oils and widening of the spray corridor with a greater main spray length and intensity. In addition stable conditions for the CMQL-supply to the manufacturing process were achieved by a lower pulsation of the CO2-oil mixture.
Keywords: CMQL; Liquid carbon dioxide; Bio-based lubricants

Initial Study on Milling in an Ultrasonically Excited Metalworking Fluid Bath - Gross, Daniel; Eichinger, Miriam; Selzam, Jan Harald; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
Energy and resource efficiency are seen as key drivers of the industrial transformation towards a low carbon economy. In particular, machine tools, which are essential to value creation, have a significant share of industrial greenhouse gas emissions due to their high-energy consumption. The energy demand for the provision and supply of metalworking fluids (MWF) alone can account for up to 25% of the total energy demand. The aim of this study is to investigate and fundamentally design an alternative cooling lubricant concept. This concept does not require continuous pumping of the coolant supply. Instead, the milling operation takes place in an immersion bath filled with metalworking fluid. An additional ultrasonic (US) actuator causes the coolant to vibrate, allowing the coolant to penetrate deeper into the cutting zone. The machining tests include a comparison of classic flood cooling, immersion bath milling and immersion bath milling with US stimulation. To compare the processes, the flank wear, the workpiece surface roughness and the bending moments due to the cutting forces were analyzed. The energy assessment allows a final evaluation of the processes.
CRIS-Team Scopus Importer:2025-02-28
Keywords: energy efficiency; immersion bath; Milling; ultrasonic

Investigation of Carbon Dioxide Based Blasting Technologies as Cryogenic Deburring Method for Titanium Alloy and Stainless Steel - Gross, Daniel; Heinz, Andrea; Amon, Sven; Meier, Trixi; Schmand, Ralf; Hanenkamp, Nico (Applied Mechanics and Materials, 2018)
This paper aims to expand the use of CO2 blasting by investigating a cryogenic deburring method for machined metallic materials. In advance to the actual deburring experiments, a streaming analysis based on high-speed video records was conducted for different blasting technologies, in order to gain deeper knowledge about their underlying active principles. For the titanium alloy Ti-6Al-4V and the stainless steel X6CrNiMoTi17-12-2, deburring experiments with three different blasting techniques were conducted and evaluated. It has been shown that cryogenic deburring has the potential to represent an alternative deburring solution for metals.
Keywords: cryogenic deburring; deburring with CO2; CO2-based blasting technologies; CO2 snow blasting; dry ice blasting

Investigation of lubricating oils from renewable resources for cryogenic minimum quantity lubrication - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
Cryogenic minimum quantity lubrication using liquid carbon dioxide (CO2) has increasingly become the focus of research in recent years. With this cooling strategy it is possible to cool and lubricate the cutting zone individually by regulating the oil and liquid CO2 flow. The oil used has a significant influence on the process stability and performance. The aim of this study is to identify the influence of 15 different base oils from renewable sources on a milling process of X2CrNiMo17-12-2 with cryogenic minimum quantity lubrication. For this purpose, a non additivated sunflower, coconut and rapeseed oil and additional bio-based oils, such as synthetic ester and fatty alcohol, will be tested and compared to a conventional mineral oil regarding wear, process forces and productivity. In addition, the impact of the bio-based oils on rough turning of X2CrNiMo17-12-2 and finishing turning of 100Cr6 with cryogenic minimum quantity lubrication is evaluated and compared to the milling performance. The results have been analyzed in comparison to conventional emulsion flood cooling and recommendations have been given for the future development of sustainable lubricants to be applied with cryogenic cooling strateg
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide

Investigation of the influence of lubricating oils on the turning of metallic materials with cryogenic minimum quantity lubrication - Gross, Daniel; Bigelmaier, Matthias; Meier, Trixi; Amon, Sven; Ostrowicki, Nicolai; Hanenkamp, Nico (Procedia CIRP, 2019)
Nowadays, cooling and lubrication for cutting processes in industry are mostly based on flood cooling. The enormous quantities of lubricants are not only harmful for the environment and employees, but also require additional infrastructure and pre-treatment, while processed parts require an additional cleaning step due to metallic swarf which leads to high manufacturing costs. The cryogenic minimum quantity lubrication could serve as an alternative cooling and lubrication concept, which might be suitable for high-alloyed steels and titanium alloys as well. Within this work the potential of this new concept of cooling and lubrication was investigated by the utilization of different lubricants for turning of Ti6Al4V, X5CrNi18-10 and 42CrMo4 workpieces with a main focus on cutting forces, tool wear and resulting surface roughness. Required data indicates that the cryogenic minimum quantity lubrication might indeed be suitable to replace the conventional wet processing routes. The proper lubricants are selected to match the material to be machined.<br
Keywords: Turning; Cryogenic Machining; Minimum Quantity Lubrication; Ti6Al4V; 42CrMo4; X5CrNi18-10

Investigation of the influence of the additivation of a biological metalworking oil in cryogenic machining - Meier, Trixi; Seydaack, Milena; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2022)

Investigation on the productivity of milling Ti6Al4V with cryogenic minimum quantity lubrication - Gross, Daniel; Appis, Maximilian; Hanenkamp, Nico (MM Science Journal, 2019)
Because of its unique material properties, Ti6Al4V is used for components in the aerospace industry which are subject to high mechanical and thermal loads. Due to that, this material is considered as difficult to cut from a machining point of view. In order to improve productivity in machining Ti6Al4V the use of an effective cooling and lubrication strategy is necessary. This challenge can be managed with the innovative hybrid technology (CMQL) combining liquid carbon dioxide (CO2) and minimum quantity lubrication (MQL) being under investigation in this article. At first, investigations on the liquid CO2 release behavior and the application of oil by the CMQL were conducted. Secondly, CNC milling experiments were carried out using carbide end mills. The CMQL technique was compared to MQL and flood cooling in respect to tool wear, cutting moment and surface integrity. For the milling operations the cooling parameters of the CMQL as well as the cutting parameters were modified, in order to reduce tool wear or increase productivity. The analysis revealed that the development of an appropriate CO2 free jet and a continuous application of oil by the CMQL is achievable without changing the state of aggregation of CO2 from liquid to supercritical. The analysis of the milling experiments indicated that CMQL is more advantageous compared to flood cooling and MQL for higher cutting parameters.<br
Keywords: Carbon dioxide; cryogenic; CMQL; Ti6Al4V; milling; spray test

KryoLEAN: Nutzung CO2-basierter, kryogener Technologie zur Zerspanung und Reinigung - Gross, Daniel (zum 3. Green Factory Bavaria Kolloquium 2016 Energieeffiziente Produktion, 2016)
Keywords: Kryogen; Zerspanung; Entgratung; Kohlenstoffdioxid; Fräsen

Milling of Ti6Al4V with carbon dioxide as carrier medium for minimum quantity lubrication with different oils - Gross, Daniel; Blauhöfer, Markus; Hanenkamp, Nico (Procedia Manufacturing, 2020)
Machining of difficult-to-cut materials such as nickel-based or titanium alloys lead to high static, dynamic and thermal tool loads. A crucial role is given to the used cooling lubricant. Here, the cryogenic cooling with liquid nitrogen or carbon dioxide has been investigated in recent years as a possible alternative to conventional flood cooling. The following article deals with the further development of CO2-based cryogenic cooling combined with a minimum quantity lubrication (MQL) injected directly into the liquid CO2 phase. The focus of the investigation is the experimental selection of MQL oils for this application. For this purpose, the potential of various base oils and additivated lubricants for the CO2 assisted milling of Ti6Al4V has been investigated. The suitability assessment of the lubricants has been based on the optical measurement of wear progress along the cutting edge, recording the effective cutting forces and surface roughness. Furthermore, a mathematical compensation method is presented for the compensation of the measured value drift caused by low temperatures. The results show that the potential of cryogenic MQL is largely determined by the base oil being used. It has also been demonstrated that the use of bio-based ester oils for the present process is an alternative to mineral oil-based lubricants.<br
Keywords: CMQL; milling; Titanium; force measurment

Sustainable Dry Turning of Aluminum Alloys Using Pulsed High-Pressure Cryogenic Jet Cooling - Selzam, Jan Harald; Enslein, Niklas; Gross, Daniel; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
As well as producing contamination-free parts, dry machining is a sustainable alternative to conventional machining processes using metalworking fluids. Despite these benefits, chip breaking and chip removal are challenges in dry machining processes, particularly when turning ductile materials, which are known for continuous chip formation and therefore long chips. Due to their tendency to become entangled around machine components, these chips have to be removed manually, posing a risk to productivity and operator health. Recent studies have demonstrated the effectiveness of pulsed high-pressure emulsion cooling for chip breaking. This paper aims to transfer these findings to sustainable dry machining and investigates the influence of pulsed high-pressure cryogenic jet cooling on chip breaking and chip removal. Therefore, liquid CO2 at pressures up to 200 bar is used as a cooling medium in turning processes of two aluminum alloys and is applied continuously or pulsed to the machining area. It has been shown that high-pressure cryogenic jet cooling improves chip breaking and chip removal, allowing a wider range of cutting parameters, widening the process window and providing a higher level of sustainability, productivity and safety in dry machining.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Aluminum; Carbon dioxide; Dry turning; Pulsed high-pressure cryogenic jet cooling; Sustainable machining

Theoretical Investigation of the Influence of Different Chamber Geometries on the Agglomeration Capacity of Carbon Dioxide - Gross, Daniel; Ferguson, Nikolas; Amon, Sven; Hanenkamp, Nico (Applied Mechanics and Materials, 2017)
This paper addresses the complicated process of carbon dioxide particle formation (agglomeration), which is essential for carbon dioxide snow blasting. Most effective process methods in this field possess a dedicated location where agglomeration is likely to occur. Research has shown that successful agglomeration is a key factor when cleaning or deburring with solid carbon dioxide. The following describes the mechanisms of carbon dioxide (CO2) snow agglomeration inside this so-called agglomeration chamber. The elements of larger size, as well as an irregular shape directly lead to the increase of effectiveness. Therefore, it is necessary to determine how to improve this process for the purpose of dealing with difficult workpieces and materials and broaden the possibilities of carbon dioxide blasting. One of the main factors of agglomeration is turbulence. In short, the more turbulent activity that takes place, the better is the particle formation of solid carbon dioxide. Numerous geometries were created with different inserts, such as static mixers or angled tubes, in hope to increase turbulence. The basic idea is to implement these geometries in computational fluid dynamics (CFD) and finally proceed to an evaluation and comparison of the simulation results, in order to select the best candidates for optimization and realization.
Keywords: Agglomeration; Carbon Dioxide; Computational Fluid Dynamics (CFD)